2014
DOI: 10.1002/ange.201308924
|View full text |Cite
|
Sign up to set email alerts
|

A Permanent Mesoporous Organic Cage with an Exceptionally High Surface Area

Abstract: Recently, porous organic cage crystals have become a real alternative to extended framework materials with high specific surface areas in the desolvated state. Although major progress in this area has been made, the resulting porous compounds are restricted to the microporous regime, owing to the relatively small molecular sizes of the cages, or the collapse of larger structures upon desolvation. Herein, we present the synthesis of a shape-persistent cage compound by the reversible formation of 24 boronic este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
72
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 54 publications
2
72
0
Order By: Relevance
“…3a,b,e). This is among the highest surface areas 6 reported for a porous molecular organic solid, 18,35,36 and significantly higher than any of our analogous tetrahedral imine cages. 19,21 Racemic co-crystals of tubular cages DFT dimer calculations were performed to establish whether chiral recognition between cages might induce heterochiral window-to-window packing and hence the formation of isostructural nanotubes (Supplementary Information, Section 4.2, Supplementary Table 7).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…3a,b,e). This is among the highest surface areas 6 reported for a porous molecular organic solid, 18,35,36 and significantly higher than any of our analogous tetrahedral imine cages. 19,21 Racemic co-crystals of tubular cages DFT dimer calculations were performed to establish whether chiral recognition between cages might induce heterochiral window-to-window packing and hence the formation of isostructural nanotubes (Supplementary Information, Section 4.2, Supplementary Table 7).…”
mentioning
confidence: 55%
“…3 POCs are rigid molecules with a permanent internal void that is accessible to guests via 'windows' in the cage. [17][18][19] Control of structure and function for POCs can be difficult, however, because slight changes in the molecular structure 19 or the crystallization solvent 20 can cause a profound change in the crystal packing. Chiral window-towindow interactions (Fig.…”
mentioning
confidence: 99%
“…Unfortunately, highly porous crystal structures of discrete molecules are rare and difficult to predict a priori 7 ; furthermore, even when a small molecule can be organized into a porous structure, such structures are typically fragile after solvent removal. Recent work by Chen 8,9 , Cooper 10-12 , Mastalerz [13][14][15][16][17][18][19] and others [20][21][22] , has resulted in molecular crystals characterized by high porosity. These noncovalently held structures can be intrinsically or extrinsically porous.…”
mentioning
confidence: 99%
“…Mastalerz et al have reported intrinsically porous molecular crystals with surface areas over 3,500 m 2 g À 1 (ref. 18), and extrinsically porous ones with surface areas 43,000 m 2 g À 1 (ref. 14).…”
mentioning
confidence: 99%
“…Most of these polyhedra are highly symmetric and achiral202122232425, and chiral molecular polyhedra with lower symmetry have attracted more and more attention because they increase the complexity of motifs and may bring more sophisticated functions262728293031. Generally, the construction of chiral molecular polyhedra follows two strategies: to use predetermined 3D chiral building blocks as the edges3032, vertices3334 or faces3536 of polyhedra to transfer 3D chirality of the components to the 3D chirality of the chiral structures, or to use achiral components to generate chiral metal-organic polyhedra373839404142 during a self-assembly process.…”
mentioning
confidence: 99%